Industrial training report: Mitechsoft Resources Sdn Bhd (Kuala Terengganu) / Muhammad Naim Muhamad - Muhamad, Muhammad Naim (Perpustakaan Tengku Anis, 2016)
The industrial training is compulsory for Faculty of Information Management students. This report is written based on five months practical training at MITECHSOFT RESOURCES SDN BHD. This report consists of four chapters which compiles all the industrial training activities, system management process and others. Basically, all the staffs at Mitechsoft need to apply leave by using paper based form. It will be difficult if the form is being damage. In addition, they need to make sure to have copies of the form in their hand. This method of leave request makes the process become hard for the staff Therefore, -the trainee developed a system EZ Request Mitech.